(untitled) - Roen, Duane H. (New York, 2012)
Meeting the objective of any composition course by putting students on the path to becoming successful writers, The McGraw-Hill Guide teaches students how to use a sequence of writing goals that can be adapted to any situation. In this manner it is easily adapted to any composition program or any individual instructor's needs by providing a consistent measure of outcomes across courses.
Keywords: English language,Tiếng Anh; Rhetoric,Study and teaching,Tu từ học,Dạy và học